Thaiwisdom perfume packaging design / Jitima Suathong and Warapon Wongsarod - Suathong, Jitima; Wongsarod, Warapon (2019)
Thai perfume is one of the Thai wisdoms is a heritage until present days. However, there is no specific study on graphic identity on Thai wisdom perfume. The objectives of this research are 1) to find out graphic guidelines for Thai traditional perfume products. 2) to investigate graphic and graphic on packaging development for the LaOng Siam, a Thai perfume brand. This research is a qualitative and quantitative research. The tools to collect data are questionnaires and structured interview form. The population are; the target group of the brand; 100 female respondents who live in Bangkok, age 20-30 years old and 10 graphic designers. The results of design guidelines are as follow; the primary display panel mainly shows Logo and illustration. The illustration should be created as graphic pattern in order to represent the main ingredients of the perfume and communicate the fragrance. The appropriate logo design is Initial Letter Mark as it is simple and shows charm and elegance. The appropriate font is Serif font. The appropriate color is any color, mix it with gold color. In addition, the use of color and the graphic pattern should represent the Thai traditional perfume characteristic and shows the wisdom’s background. The graphic design development for LaOng Siam are as follows; Mood & Tone: natural, elegant and charming. Color: Gold and Thai tone colors. The logo should be mainly gold color. Graphic on the primary display panel: Thai graphic style mixes with modern graphic style, and should show the identity of each odor clearly.